A systematic review of the experience of older women living and coping with type 2 diabetes. Issue 2 (2nd September 2013) - Li, Jiemin; Drury, Vicki; Taylor, Beverley
<x xml:space="preserve">Abstract</x> This paper reports on a systematic review that sought to answer the research question: what is the experience of women living and coping with type 2 diabetes? A range of relevant terms were identified and electronic databases were searched. Only qualitative studies that explored the meaning of living and coping with type 2 diabetes and that included adult women aged ≥ 18 years were considered. We found evidence that women are challenged by their multi‐caregiving roles and the complexities of managing their diabetes simultaneously. For female patients with diabetes, holistic care and individual psycho‐education programmes appear to be facilitate more effective and successful diabetes management. In addition, carer programmes that provide information so that family and friends can support and assist the woman with diabetes are required.